Biosynthesis of Lipoxygenase Products by Enzyme Preparations from Normal and Psoriatic Skin - Ziboh, Vincent A.; Casebolt, Tamara L.; Marcelo, Cynthia L.; Voorhees, John J. (Journal of investigative dermatology, 1984)
Incubations of [14C]arachidonic acid ([14C]AA) with cell-free preparations from normal, clinically involved and uninvolved epidermis from psoriatic subjects resulted in the formation of several radiolabeled metabolites of the lipoxygenase pathway. The identities of the monohydroxy-ETEs and dihydroxy-ETEs (products of the 12-lipoxygenase and 5-lipoxygenase pathways) were determined by comparison with authentic standards of 12L-hydroxy-5,8,10,14-eicotetraenoic acid (12-HETE) and authentic 5S,12R-dihydroxy-6,8,10, 14-eicosatetraenoic acid (LTB4) by thin-layer chromatography in two solvent systems; by silicic acid column chromatography and by normal phase and straight phase high-pressure liquid chromatography. Activity of the enzymes which catalyze this transformation are localized in the soluble (105,000 g supernatant) fraction of the epidermal preparations. The activity of enzymes of both pathways were inhibited by 5,8,11,13-eicosatetraynoic acid (ETYA) and nor-dihydroguaretic acid (NDGA), known inhibitors of the lipoxygenase and cyclooxygenase pathways. Transformation of [14C]AA into [14C]LTB4-like metabolite by the soluble preparations from clinically involved psoriatic epidermis was significantly higher (p < 0.001) than from paired uninvolved soluble preparations or from soluble preparations from normal subjects. Furthermore, biosynthesis of LTB4-like metabolite by the uninvolved soluble preparation was significantly higher (p < 0.05) than preparations from normal epidermis. These results imply that the [14C]LTB4-like metabolite biosynthesized by the clinically involved soluble preparation was due at least in part to the increased activity of the lesional enzymes and not entirely due to possible intraepidermal infiltrating neutrophils. Human epidermal preparations, therefore, contain enzymes which catalyze the transformation of labeled AA into LTB4-like metabolite as well as into other yet unidentified dihydroxy-ETEs. Localization of a soluble 5-lipoxygenase-like activity in the epidermis implies a possible role of the lipoxygenase products in the proliferative and inflammatory processes in this tissue.